Soil properties during transition from conventional to organic farming system in Kavre District, Nepal - Maharjan, Biboss; Chaulagain, Anon; Sapkota, Parikrama; Gauchan, Dhurva P.; Lamichanne, Janardan (Kathmandu University Journal of Science, Engineering and Technology, 2018)
The aim of this study was to investigate the response of soil physical and chemical properties during the transition from conventional to organic farming system. Soil samples were collected from five different farms: “Hasera organic farm” under 10 years of organic farming, “Everything organic nursery” under 5 years of organic farming, “Grameen Krishi” under 3 years of transition from conventional to organic, “Gautamshree farm” under 1 years of transition from conventional to organic and “Kuntabeshi farm” under IPM practice as reference. Soil bulk density, moisture content, texture, NPK, CEC and soil organic matter was evaluated in soil samples collected at 0-15 cm. Soil organic matter (5.45%) was highest in Hasera farm, whereas lowest bulk density (1.02gcm-3) was also in Hasera farm. Lowest soil organic matter content was found in Gautamshree farm. Soils of all farms were under loam texture. Soil macronutrients were highest in Grameen Krishi farm. The overall pH value of all soil samples was slightly acidic to acidic.Kathmandu University Journal of Science, Engineering and TechnologyVol. 13, No. 1, 2017, Page: 76-84